2020
DOI: 10.1007/s00415-020-10141-w
|View full text |Cite|
|
Sign up to set email alerts
|

Pre-existing cerebrovascular disease and poor outcomes of COVID-19 hospitalized patients: a meta-analysis

Abstract: Background Due to pro-inflammatory and hypercoagulation states, COVID-19 infection is believed to increase the risk of stroke and worsen the outcomes of the patients having pre-existing cerebrovascular diseases (CeVD). There is limited literature on prevalence of pre-existing CeVD in COVID-19 patients, and outcomes are unknown. The objective of this meta-analysis is to evaluate the outcomes of COVID-19 patients with pre-existing CeVD. Methods English full-text-observational studies having data on epidemiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 31 publications
4
23
0
Order By: Relevance
“…This result has been based on considering 852 patients (603 survivors and 249 non-survivors) with confirmed SARS-CoV-2 infection from four retrospective Chinese studies. Several meta-analyses confirmed such association [ [139] , [140] , [141] ]. Particular precautions should be taken in the management of COVID-19 patients with preexisting cerebrovascular disease.…”
Section: Interrelation Between Covid-19 and Disorders With Mixed Or Mmentioning
confidence: 86%
“…This result has been based on considering 852 patients (603 survivors and 249 non-survivors) with confirmed SARS-CoV-2 infection from four retrospective Chinese studies. Several meta-analyses confirmed such association [ [139] , [140] , [141] ]. Particular precautions should be taken in the management of COVID-19 patients with preexisting cerebrovascular disease.…”
Section: Interrelation Between Covid-19 and Disorders With Mixed Or Mmentioning
confidence: 86%
“…Literature has revealed that novel coronavirus in patients with pre-existing neurological diseases is associated with poor outcomes [ 39 , 40 ]. A study in Spain indicated that chronic neurologic disease is among the most relevant comorbidities of COVID-19 [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…This results in highly increased D-dimer fibrin, which is now considered to be a risk factor of disease severity and mortality [73]. Indeed, COVID 19 patients with a previous history of cerebrovascular disease have higher risk of severe COVID-19 than those without (RR 2.07] [74]) and 2.67 higher odds for poor outcome, including the need for intensive care admission and mechanical ventilation, as well as higher rate of mortality [75].…”
Section: Hypercoagulopathy and Strokementioning
confidence: 99%